Emphasising Personal Investment Effects Weight Loss and Hedonic Thoughts about Food after Obesity Surgery - Margaret Husted; Jane Ogden (Hindawi Limited, 2014)
Obesity surgery is the most effective treatment method for the severely obese but does not work for everyone. Indications are that weight-loss success may be related to individuals' sense of investment in surgery, with failure linked to higher automatic hedonic motivations to consume food and greater susceptibility to food in the environment. A pilot study using an independent experimental design recruited bariatric surgery patients (n=91) via a UK obesity-surgery charity website who were randomly allocated to either the intervention or the control condition. The intervention involved raising the salience of the personal investment made in having weight-loss surgery in an attempt to reduce automatic hedonic thoughts about food and aid weight loss. Data was collected initially with subsequent weight loss measured at 3 months of follow-up. Following the intervention, participants reported significantly reduced hedonic thoughts, increased liking for low-fat foods, reduced liking of high-fat food, and higher self-efficacy for achieving sustained weight loss than controls. By 3 months, this was translated into significant differences in mean weight losses of 6.77 kg for the intervention group and 0.91 kg for control participants. To conclude, a quick simple cost-effective intervention encouraging participants to focus on investment helped weight loss and changed hedonic thoughts about food in bariatric patients.